Resistive switching RAM devices based on amorphous oxide semiconductors for system on panel applications - Paulo, João Francisco Carvalho (2019)
This work reports the mask design, fabrication and characterization of memristor devices with diode like electrical behavior at pristine state. It is due to the presence of Schottky junctions between Zinc-tin-oxide (ZTO) and platinum - Indium-galliumzinc- oxide (IGZO) and molybdenum oxide for two different Metal-Insulator-Metal (MIM) configurations. The devices were exclusively produced using physical vapor deposition processes without intentional heating. Typical advanced electrical analysis of ReRAM device was performed. The Pt-ZTO-TiAu devices showed pinched hysteresis properties with large Ron=of f ratio, fast switching which can be controlled in a digital SET and analog RESET operation. However, large device-to-device variations and stability are the main issues which is due to the processing. On the other hand, the Mo-IGZO-Mo devices showed a small Ron=of f ratio and only analog operation. There was a high yield and stability. However, using DC sweep for cycling led to a charging phenomenon. Using SET/RESET pulses, the devices sustain hundreds of cycles without deterioration or movement of the resistance states, showing great resilience and retention.